Internet of Things for the Distributed Generation - (:unkn) unknown (IEEE, 2019)
The Internet of Things refers to any object or device that automatically sends and receives data over the Internet. This rapidly expanding concept is now being used as the Internet of Everything. This structure includes sensors and devices that interact with people and share information. In this study, the distributed generation system consisting of wind, solar and hydrogen energy was remote monitored through an interface in the internet of things (IoT).
Keywords: distributed generation; internet of things; energy monitoring